কল্লোল, ভাগ ২, সপ্তম শ্রেণী - (:unkn) unknown (Bihar State Text Book Corporation Limited, 2015)
This book is a Bengali textbook for Seventh standard (Class VII) of Bihar secondary school board.
Kallol, Part 2, Class VII
Keywords: Bengali; Literature; Bengali; Bengali